Loop-based RSA Key Generation Algorithm using String Identity - Norhidayah, Muhammad; Jasni, Mohamad Zain; Md Yazid, Mohd Saman (IEEE, 2013)
This paper will propose i-RSA algorithm, this algorithm is focus on key generation algorithm. Enhancement of this algorithm is user identity can be used as a public key such as email address. Previous algorithm was successful used email identity as a public key, but not all type of email can used as a public key. So we propose i-RSA algorithm that can produces 66.6% compared to previous algorithm (46.67%) email can be a string public key. The differences between i-RSA and previous algorithm are looping process in key generation, to get new value of p and q parameter, looping process will stop when value of k is equal to 1, and the email can be a public key. RSA algorithm and CRC 32 hash function will be explain in preliminaries section. Detail explanations of i-RSA algorithm in propose algorithm section. In future, i-RSA algorithm can be improved, so that 100% of email can be a public key.